Absent Contrast Filling of Ipsilateral Superficial Middle Cerebral Vein Predicts Midline Shift in Acute Middle Cerebral Artery Occlusion - Zhang, Sheng; Lin, Longting; Zhang, Ruiting; Wang, Meiping; Yu, Yannan; Shi, Zongjie; Parsons, Mark; Geng, Yu (Frontiers in Neurology, 2020)
Background and purpose Midline shift is a life-threatening complication of acute large artery occlusion (LAO). The value of superficial middle cerebral vein (SMCV) for predicting midline shift is currently unclear for patients with acute LAO. Methods Consecutive acute LAO (middle cerebral artery M1±intracranial internal carotid artery) patients between March 2018 and May 2019 were included. Absent filling of ipsilateral cortical vein (marked as SMCV-) was defined as no contrast filling into the vein across the whole venous phase of four-dimensional CT angiography derived from CT perfusion in the ischemic hemisphere. Results In the total of 81 patients, 31 (38.4%) were identified as SMCV-. SMCV- independently predicted midline shift, with sensitivity of 87.5% and specificity of 82.5%. Receiver operating characteristic analysis showed that, including SMCV- as a predictor in addition to baseline ischemic core volume significantly increased the area under the curve in predicting midline shift (SMCV- with baseline ischemic core volume vs baseline ischemic core volume: AUC=0.903 vs 0.841, Z=2.451, P=0.014). Conclusion In acute LAO patients, the presence of SMCV- was a sensitive and specific imaging marker for midline shift. SMCV- had supplementary value to baseline ischemic core volume in predicting midline shift.